Reducing seed losses and fuel consumption in rapeseed harvest - Špokas, L.; Smolinskiy, S. V.; Žebrauskas, G.; Čiplienė, A. (НУБіП України, 2018)
Rapeseed harvesting starts in the Baltics as soon as seed moisture content decreases to 12%. While the variation in seed moisture content is not affected by short-term precipitation, prolonged precipitation leads to ca. 2% increase in the moisture content. 0.2 m high stubble of winter rapeseed accounts for the share of 49.87% in the total stem mass. Its moisture content is 10.39% higher than of the remaining share of the stem mass. Increase of the stubble height to 0.3 m leads to 15.52% reduction in the stem mass fed into a combine harvester, and 1.79% reduction in moisture content of the stem mass. In this case, fuel consumption per hectare of harvested rapeseed is lower by 2.74 l, and per ton of threshed seeds – by 0.27 l. Relationship between the rate of rapeseed feed into a combine harvester, shatter loss from straw separation and chaff cleaning, and fuel consumption per ton of threshed seeds has been found. The rate limit of rapeseed feed into the combine harvester is reached, when fuel consumption per ton of threshed seeds has stopped reducing, but shatter loss from straw separation and chaff cleaning is still within the tolerable range. In the case of winter rapeseed harvesting under processing conditions, fuel consumption per ton of threshed seeds ranged from 2.5 to 6.5 l, while in the case of rational rate of rapeseed feed into the combine harvester, fuel consumption per ton of threshed seeds reached 2.93±0.23 l.
Зниження витрат насіння і витрата палива у врожаю ріпаку
Ріпаку збір урожаю починається в Прибалтиці, як тільки вологість насіння знижується до 12%. В той час як зміна вологості насіння не впливає на короткочасні опади, тривалі опади призводить до Ка. 2% збільшення вмісту вологи. Висока 0,2 м стерні озимого ріпаку припадає на частку 49.87% у загальній стовбурної маси. Її вологість становить 10.39% вище, ніж інша частка стовбурної маси. Збільшення висоти стерні до 0,3 м приводить до зменшення 15.52% в стовбурі маса подається в комбайні, і зниження 1.79% вологості маси стебла. У цьому випадку, витрата палива на гектар ріпаку намолочено буде нижче на 2,74 л, а на тонну обмолоченого зерна – на 0,27 л. Зв'язок між швидкістю ріпаку годувати в комбайні, зруйнувати втрати від розділення і очищення соломи, полови, і витрата палива на тонну обмолоченого Насіння був знайдений. Граничний розмір насіння ріпаку годувати в комбайні досягається, коли витрата палива на тонну обмолоченого насіння припинив зниження, але зруйнувати втрати соломи розділення і очищення полови-це ще в межах допустимого діапазону. У разі озимого ріпаку заготовка під обробку умови, витрата палива на тонну обмолоченого насіння варіювалася від 2,5 до 6,5 л, а у випадку раціональних вартість насіння ріпаку кормової комбайн, витрата палива на тонну обмолоченого насіння доїхати 2.93±0,23 л.
Keywords: combine harvesters; rapeseed; fuel consumption; grain loss; throughput; зернозбиральний комбайн; ріпак; витрата палива; втрати зерна; пропускна здатність